Pengaruh Penggunaan Media Pembelajaran QuizWhizzer Terhadap Motivasi Belajar Siswa di SMA Swasta Istiqlal Deli Tua - Safira Lubis, Nazia; Siar Meiriza, Mica (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of using the QuizWhizzer learning media on students' learning motivation in the topic of employment. The issue of low student motivation in economics subjects highlights the need for innovative learning strategies that can stimulate engagement. This research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group. The participants were eleventh-grade social science students at SMA Swasta Istiqlal Deli Tua, divided into an experimental group and a control group. Students' learning motivation was assessed indirectly through the improvement in learning outcomes (pretest and posttest scores) and observations of student engagement during the learning process. The results showed that the average posttest score in the experimental group was significantly higher than that of the control group, with a gain score of 0.65 (moderate–high category), while the control group only achieved a gain score of 0.30 (low–moderate category). The independent sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between the two groups. Therefore, it can be concluded that the use of QuizWhizzer learning media has a positive effect on increasing students' learning motivation in the employment topic.